Sensitivity Analysis Comparisson of Synthetic Polymer and Biopolymer using Reservoir Simulation - Romal Ramadhan; Muslim Abdurahman; Falan Srisuriyachai (Testing Center for Oil and Gas LEMIGAS, 2020)
With a simultaneous increasing demand for oil and large decreases worldwide in newly discovered oil reserves in the past few decades, much attention has been paid to more effi cient production approaches such as enhanced-oil-recovery (EOR) methods for developing oil and gas from existing reservoirs (Li et al., 2014). Basically, there are two types of polymers; biopolymers and synthetic polymers (Cenk et al., 2017). Method used for this study is reservoir simulation by Computer Modeling Group (CMG) STARS simulator. The study concerns to investigate and analyze the polymer sensitivity on two diff erent types of polymer: synthetic polymer and biopolymer. The simulation is done on 15x15x4 grid for 3653 days (10 years). The simulation indicates that the biopolymer injection shows more stable result in compare to synthetic polymer. The biopolymer’s adsorption occurs on smaller area and takes longer time. Conversely, the adsorption of synthetic polymer goes on bigger area of the reservoir and transpire on shorter time. Considering these facts, the use of biopolymers is more eff ective in order to increase the sweep effi ciency by reducing viscous fi ngering of chemical injection in reservoir.